Metastatic Primary Angiosarcoma of the Breast: Can We Tame It the Metronomic Way - Pramanik, Raja (Indian J Med Paediatr Oncol, 2017)
Primary angiosarcoma of the breast is a highly aggressive but rare malignant neoplasm. Palliative chemotherapy with different agents and combinations has been tried in the metastatic setting with poor results. We present the case of a young woman with this disease describing her aggressive course. We used a metronomic combination of oral drugs due to her poor general condition and achieved disease stabilization although not durable.